Hospitalitas sebagai virtue kepemimpinan dalam meningkatkan kinerja guru pendidikan agama Kristen - Rogahang, Heldy Jerry; Umar, Sry Nurmawati; Massang, Berdinata (KURIOS, 2022)
This research aims to determine whether there is an influence of the principal's leadership on teacher performance at SMTK North Sulawesi. The research method used is associative quantitative research using non-random sampling, namely purposive sampling. Data on general and Christian principal leadership and teacher performance were obtained using a Likert measurement scale. The data analysis techniques used are simple regression analysis, T test and coefficient of determination. The research results show that there is a significant influence between classroom management on learning motivation for Christian Religious Education through the equation Y=32.821+0.828X with a correlation coefficient of 0.974. This means that the better the principal's leadership, the higher the teacher's performance. Furthermore, the results obtained from calculating the coefficient of determination show that there is an influence of the principal's leadership on teacher performance of 93.2% and the remaining 6.8% is influenced by other factors not examined by researchers.